The Croatian Lemmatization Server - Tadić, Marko (Array, 2005)
The need for lemmatization in inflectionally rich languages is indisputable: it is applicable for the whole range of procedures, from text-search up to parsing. From two predominant approaches to lemmatization (algorithmic— generally rule-based and realized with FSA— and relational— generally data-driven and realized with databases), this paper opted for the latter. The reason is that formal-grammar approaches to Croatian morphology are rare and limited just to a part of morphological system. The other reason is that the generator for Croatian has already been developed (Tadić 1994) as well as Croatian Morphological Lexicon (CML) (Tadić and Fulgosi 2003). The idea was to offer an on-line lemmatization, POS/MSD service using CML v4.5 as the back-end. The Croatian Lemmatization Server (CLS) is available at http://hml.hnk.ffzg.hr, and it offers lemmatization and POS/MSD tagging at unigram level for now. For each token in submitted text, the server delivers all possible lemmas of which this token may be a word-form. For homographic tokens, each lemma is accompanied with all possible POS/MSD tags which are compliant to MulTextEast v3 specifications for Croatian. The CLS can also be used for generation: when lemma is inputted and marked, all its possible word-forms are being retrieved and delivered.